Youth experiencing homelessness at risk for suicide: psychosocial risk factors and service use patterns - Laura J. Chavez; Kelly J. Kelleher; Alicia Bunger; Xin Feng; Margaret Fitzpatrick; Jodi L. Ford; Allen B. Mallory; Arielle H. Sheftall; Tansel Yilmazer; Alexis Pizzulo; Jesse L. Hawke; Mattina A. Davenport; et al. (BMC Public Health)
Abstract Objective Young adults experiencing homelessness often suffer from adverse mental health outcomes and suicide is a leading cause of death. The objective of this study is to examine service use and psychosocial risk factors for suicide, in relation to suicide risk assessment, to inform strategies for engaging youth in suicide prevention services. Methods A cross-sectional analysis of youth enrolled in a supportive housing randomized clinical trial. We categorized suicide risk into three groups (low-, moderate-, and high-risk) based on suicidal ideation and past-year suicide attempt. The service use patterns across these groups are described, as well as other psychosocial risk factors (psychiatric comorbidity, depressive symptoms, substance use, and sleep impairment). Results Among 193 enrolled youth, 126 (65.3%), 32 (16.6%), and 35 (18.1%) were categorized as low-risk, moderate-risk, and high-risk for suicide, respectively. A high proportion of youth reported ever having been diagnosed with a psychiatric disorder (57.5%) and cannabis was the most heavily used substance. However, only a minority of youth received medical care or mental health services in the past 3 months, 40% and 34%, respectively. Even fewer youth received mental/emotional health services in the past 3 months (15%), though use was highest among the high-risk group (34%). Conclusion Understanding the needs of youth experiencing homelessness who are at risk for suicide is critical to developing interventions to alleviate their risk for suicide. Given that the use of medical and mental health care is low among this population, more active outreach strategies may be warranted to deliver prevention interventions.